Service Quality, Product Quality, Customer Satisfaction and Brand Loyalty in E-Commerce: Interplay and Mediation Analysis - Ronny H. Walean; Noufer A. Tumbelaka; Nadia C. G. Tumober; Deske W. Mandagi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the relationships between product quality, service quality, customer satisfaction, and brand loyalty within the context of e-commerce, with a specific focus on Shopee, a leading e-commerce platform in Southeast Asia. Using a cross-sectional survey design, the research examines the impact of two exogenous variables—product quality and service quality—on customer satisfaction, as well as the mediating role of customer satisfaction in influencing brand loyalty. The research was conducted with 220 respondents and analyzed through Structural Equation Modeling (SEM) using SmartPLS. The findings reveal that both product quality and service quality significantly influence customer satisfaction. However, service quality alone does not have a direct effect on brand loyalty. Importantly, customer satisfaction plays a critical mediating role, especially between service quality and brand loyalty. These results highlight the importance of enhancing customer satisfaction to foster brand loyalty, offering valuable insights for businesses seeking to improve their service offerings and strengthen customer loyalty. The study suggests that companies should prioritize customer satisfaction as a key mediator in their service and quality strategies.